EXPLORATION OF ANTI-EPILEPTIC PROPERTY OF METHANOLIC EXTRACTION OF OCIMUM BASILICUM - Ray, J; Rout, M; Prusty, S; Mohanty, R; Sahu, P (Journal of Global Pharma Technology, 2024)
The goal of the current investigation was to determine if a methanolic extract of Ocimum Basilicum (O.B.) leaves could protect against phenytoin induced Epilepsy. Epilepsy was studied using dosages of 400mg/kg is more effective than 200 mg/kg of methanolic extract of O.B. The extract was administered, which improved improve behavioral disturbances, oxidative stress can be reduced and antioxidant enzymes can be recovered. The results of this investigation showed that rats treated with a methanol extract of O.B. leaves have neuroprotective potential. Therefore, it can be inferred that Ocimum basilicum may be useful in the treatment of Epilepsy disease. Keywords: Ocimum Basilicum (O.B), Leaves, Phenytoin, Rat.